Recent advances in renal imaging [version 1; referees: 3 approved] - Joshua Thurman (F1000Research, 2018)
Kidney diseases can be caused by a wide range of genetic, hemodynamic, toxic, infectious, and autoimmune factors. The diagnosis of kidney disease usually involves the biochemical analysis of serum and blood, but these tests are often insufficiently sensitive or specific to make a definitive diagnosis. Although radiologic imaging currently has a limited role in the evaluation of most kidney diseases, several new imaging methods hold great promise for improving our ability to non-invasively detect structural, functional, and molecular changes within the kidney. New methods, such as dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and blood oxygen level-dependent (BOLD) MRI, allow functional imaging of the kidney. The use of novel contrast agents, such as microbubbles and nanoparticles, allows the detection of specific molecules in the kidney. These methods could greatly advance our ability to diagnose disease and also to safely monitor patients over time. This could improve the care of individual patients, and it could also facilitate the evaluation of new treatment strategies.